Elaborating Cash Waqf Development In Indonesia Using Analytic Network - Rusydiana, Aam Slamet; Devi, Abrista (International Journal of Islamic Business and Economics (IJIBEC), 2018)
This research is aim to identify the priority factors that being barrier to develop the practice of cash waqf in Indonesia using Analytic Network Process (ANP) method. Here is also offered some solutions for the problems identified. ANP is a mathematic theory that allows one to deal systematically with dependence and feedback and that can capture and combine tangible and intangible factors by using ration scale. Result show that the problems appeared in managing cash waqf in Indonesia divided into 4 important aspects, there are: Human Resource aspect, trust aspect, system aspect, and sharia aspect. The rank for most priority problems to less priority based on the priority result are: 1) trust problems (whereas the most priority for this sub-criteria is donators’ lack of trust), 2) sharia problems (is unfulfilled waqf covenants), 3) human resource problems (is misappropriation of waqf funds, 4) system problems (is weak of management systems). Strategies that can be built to develop the practice of cash waqf in Indonesia based on the priorities are: 1) more computerized cash waqf management, 2) the development of waqf education institutions, 3) more comprehensive fund manager quality improvement, 4) transparency and accountability in every step.